- #1

- 7

- 0

## Homework Statement

Solve the following initial value problem

y'' - 5y' +6y = x*exp(2x), y(0) = y'(0) = 0

## Homework Equations

## The Attempt at a Solution

Ive found the complimentary solution to be r = 3, 2,

Yg = C1*exp(3x) + C2*exp(2x) + Yp

But to find Yp is giving me the problems, using the method of undetermined coefficients, I have tried to so far

1. (Ax^3 + Bx^2 + Cx + D)*exp(2x)

2. (Ax^2 + Bx + C) * exp(2x)

3. (Ax + B)* exp(2x)

but with no luck can anyone help me with what my guess to solve it